Adventures in multibeam water column data: sharks, seeps and sediment plumes - Parnum, Iain; Ellement, Tyler; Parsons, Miles (2015)
Once focussed on the collection and processing of bathymetry data, in recent years multibeam echo-sounders and imaging SONARs have also been used increasingly to map and quantify the spatial and temporal distribution of in-water targets. The authors have used multibeam systems to study fish, marine mammals, zooplankton, epi-benthic structure, seeps and suspended sediment. Some of these studies are highlighted below. All of these applications required the need for exploration and analysis of the raw data. This resulted in the development of new software to read various SONAR data and to summarise large water column datasets. Details of these software tools and how to access them are given below